SAMS teach yourself visual C++.net in 24 hours - Simon, Richard J. (Sams, 2002)
This book is for developers who want to develop .NET applications using Visual C++ 7.0 as the programming language. It covers the new features of Visual C++ which support .NET while lightly covering the new MFC and ATL enhancements as they relate to the .NET architecture, but focuses heavily on developing for the .NET framework. The book takes the reader through a simple .NET application, a more advanced application, and Internet development in .NET. The reader is also shown the differences between managed and unmanaged Visual C++ code and how to integrate them--critical information for migrating legacy C++ applications to the .NET architecture.